Dampak Keterbatasan Sumber Daya Pendidikan terhadap Kualitas Pembelajaran Anak Usia Dini di KB Mawar Bulango Timur - Adel A. Djakaya; Reva Nesya Hamatia (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2026)
This study aims to determine the impact of limited educational resources on the quality of early childhood learning at KB Mawar Bulango Timur. The study focuses on limitations in human resources, facilities and infrastructure, learning media, financial resources, and their effects on the learning process. A qualitative descriptive approach was employed. Data were collected through observation, interviews, and documentation involving the principal and teachers as informants. Data analysis included data reduction, data presentation, and conclusion drawing. The findings reveal that educational resources at KB Mawar Bulango Timur remain limited, particularly regarding facilities, educational play equipment, learning media, operational funding, and teacher competency development. The limited number of educators also affects the learning process. These constraints reduce learning effectiveness, limit teacher creativity, decrease children’s interest and enthusiasm, and hinder the optimal development of early childhood abilities. Consequently, learning outcomes are not achieved effectively. The study concludes that limited educational resources significantly influence the quality of early childhood learning at KB Mawar Bulango Timur. Therefore, stronger support from schools, the government, parents, and the community is essential to improve educational resources and enhance learning quality.